Deploying Language Technologies for Underserved Communities - Bali, Kalika; Choudhury, Monojit; Sitaram, Sunayana; Santy, Sebastin (UNESCO International Conference on Language Technologies for all (LT4All), 2019)
Gondi, a South-Central Dravidian language in the vulnerable category on UNESCO’s Atlas of the Worlds Languages in Danger (Moseley,2010). Spoken by nearly 3 million people (India, 2011) it is also one of the least resourced languages in India, with little available data and technology. In this poster, we will present Adivasi Radio, a mobile application that provides the Gond tribal community with access to information. We believe that by focusing on Gondi, we will not only empower the Gondi community but also help understand and create a framework to serve as a guide for introducing language technologies in under-served communities.